2014
DOI: 10.1080/05704928.2014.903376
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Signal Enhancement and Noise Reduction Techniques for Tunable Diode Laser Absorption Spectroscopy

Abstract: Tunable diode laser absorption spectroscopy (TDLAS), as a noninvasive spectroscopic method, permits high-resolution, high-sensitivity, fast, in situ absorption measurements of atomic and molecular species and narrow spectral features in gaseous, solid, and liquid phases. Advances in new diode laser sources and laser spectroscopic techniques generally have triggered an increasing application of TDLAS in various disciplines (for example, atmospheric environmental monitoring, chemical analysis, industrial process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(57 citation statements)
references
References 156 publications
0
57
0
Order By: Relevance
“…A small overview, not aiming for completeness, will be given here. A comprehensive study can be found in [39]. It is worth mentioning that PICs can incorporate all of the schemes mentioned here, with negligible impact on the footprint or cost of the devices.…”
Section: Advanced Spectroscopic Methodsmentioning
confidence: 99%
“…A small overview, not aiming for completeness, will be given here. A comprehensive study can be found in [39]. It is worth mentioning that PICs can incorporate all of the schemes mentioned here, with negligible impact on the footprint or cost of the devices.…”
Section: Advanced Spectroscopic Methodsmentioning
confidence: 99%
“…However, optical interference fringe, the primary cause of background fluctuation, has not been effectively suppressed in WMS. Many methods, including the adoption of post-detection filtering and the improvement of the detection system, have been attempted to optimize the optical interference fringe in methane sensors [97]. For example, recently, a method of combining dual tone modulation (DTM) with vibration reflector (VR) was introduced, which decreased the standard deviation (STD) value of the background signal to 0.0924 ppm [98].…”
Section: Optimization Of Methane Detection Based On Wmsmentioning
confidence: 99%
“…Through an investigation of relevant literature, it has been found that there are many studies on measurements of species concentration and temperature by direct absorption spectroscopy (DAS) or wavelength modulation spectroscopy (WMS) employing isolated absorption lines of the measured gas molecules [12][13][14][15][16][17][18][19]. However, for the molecules with dense absorption spectral features (such as ethylene and methane, which contain hydrocarbon bonds), there will be self-mixing or overlap with other molecules at an elevated temperature and pressure, making it difficult to accurately infer the complete transition properties through a single line or line pair.…”
Section: Introductionmentioning
confidence: 99%